2019
DOI: 10.1073/pnas.1904480116
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic expression of viperin regulates thermogenesis in adipose tissues

Abstract: Viperin is an interferon (IFN)-inducible multifunctional protein. Recent evidence from high-throughput analyses indicates that most IFN-inducible proteins, including viperin, are intrinsically expressed in specific tissues; however, the respective intrinsic functions are unknown. Here we show that the intrinsic expression of viperin regulates adipose tissue thermogenesis, which is known to counter metabolic disease and contribute to the febrile response to pathogen invasion. Viperin knockout mice exhibit incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 48 publications
(54 reference statements)
1
37
0
Order By: Relevance
“…Inhibition of the NAD + ‐dependent enzymes such as 2‐OGDH, which catalyses transformation of 2‐OG in TCA cycle, can reduce mitochondrial respiration and affects metabolism of nucleotides causing a reduction in viral replication. (iv) It is reported that the radical‐SAM activity of RSAD2 reduces activity of the β‐oxidation pathway [16]. ddhCTP may inhibit the NAD + ‐dependent activity of enzyme 3‐hydroacyl‐CoA dehydrogenase reducing the flux through the β‐oxidation pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the NAD + ‐dependent enzymes such as 2‐OGDH, which catalyses transformation of 2‐OG in TCA cycle, can reduce mitochondrial respiration and affects metabolism of nucleotides causing a reduction in viral replication. (iv) It is reported that the radical‐SAM activity of RSAD2 reduces activity of the β‐oxidation pathway [16]. ddhCTP may inhibit the NAD + ‐dependent activity of enzyme 3‐hydroacyl‐CoA dehydrogenase reducing the flux through the β‐oxidation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the widely studied broad‐spectrum antiviral function of RSAD2 [7–14], emerging evidence suggests the enzyme may play a role in a range of different cellular processes. RSAD2 plays a role in optimal Th2 response [15], regulates thermogenesis in adipose tissue [16], is required for Golgi trafficking of TNF‐α in activated microglia [17], and regulates chondrogenic differentiation via CXCL10 protein secretion [18]. The radical‐SAM activity of RSAD2 can abolish metabolism of amino acids and mitochondrial respiration [19].…”
Section: Introductionmentioning
confidence: 99%
“…Immunoprecipitation using the HEK 293T cell lysates was performed with anti-Myc tagged magnetic beads according to the manufacturers' protocol, as detailed previously (32).…”
Section: Immunoblotting and Immunoprecipitation Assaysmentioning
confidence: 99%
“…Our results provide support for the hypothesis that HCMV co-opts viperin to inhibit HADHB and thereby facilitate the escape of viral particles from the cell. They also throw light on the recent and intriguing observation that viperin is involved in regulating thermogenesis in murine adipose tissue (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation